The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/10641950801958059
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risks of Preeclampsia and Small for Gestational Age Infant by Uterine Artery Doppler

Abstract: Women with an abnormal uterine artery Doppler great a considerably higher risk for developing preeclampsia and/or having an SGA infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Numerous studies have shown that late first trimester screening of the uterine artery in high-risk women can accurately identify a subset of women who are destined for major complications that will be attributable to placental disease. Serial Doppler assessment of the uterine artery is performed from the 16th wk onwards in these high risk women who may have history of factors known to cause IUGR 25,26 . The persistence of the pre-diastolic notch and gradually increasing impedance indices suggest an abnormal uterine circulation and hence is an indicator to treat these women with bed rest, antihypertensives and oxygen therapy right from the onset of the pathology.…”
Section: Changing Trends In Doppler Assessment Of Iugr Fetusesmentioning
confidence: 99%
“…Numerous studies have shown that late first trimester screening of the uterine artery in high-risk women can accurately identify a subset of women who are destined for major complications that will be attributable to placental disease. Serial Doppler assessment of the uterine artery is performed from the 16th wk onwards in these high risk women who may have history of factors known to cause IUGR 25,26 . The persistence of the pre-diastolic notch and gradually increasing impedance indices suggest an abnormal uterine circulation and hence is an indicator to treat these women with bed rest, antihypertensives and oxygen therapy right from the onset of the pathology.…”
Section: Changing Trends In Doppler Assessment Of Iugr Fetusesmentioning
confidence: 99%
“…This model can be evaluated by uterine artery Doppler. 11 Many studies on uterine artery Doppler have demonstrated that preeclamptic patients have more abnormal uterine artery Doppler findings than normal patients. In systematic reviews and meta-analyses, it has been suggested that the presence of a uterine artery notch or an increase of uterine artery pulsatility index (PI) are better predictors of preeclampsia in the second trimester than in the first trimester (sensitivity 77-96%).…”
Section: Introductionmentioning
confidence: 99%
“…The impaired placentation is one possible cause. 4 There are many studies that aim to evaluate risk factors of pre-eclampsia. Primigravida, previous pregnancy-induced hypertension, obesity, diabetes, hypertension and multiplicity are risk factors.…”
Section: Introductionmentioning
confidence: 99%